2017
DOI: 10.1002/ijc.30523
|View full text |Cite
|
Sign up to set email alerts
|

HPV status and favourable outcome in vulvar squamous cancer

Abstract: Impact statementThe epidemiology of vulvar cancer (VSCC) is changing. Our data reveal that the age at which women are diagnosed with VSCC is falling. High-risk (HR) human papillomavirus (HPV) infection is very common in vulvar intraepithelial neoplasia (VIN) and present in just over 50% of VSCC. HR-HPV positivity was associated with lower progression rates from VIN to VSCC and improved progression-free survival of VSCC. We have conducted a detailed population-based study to examine rates of progression of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 30 publications
(36 reference statements)
3
57
0
1
Order By: Relevance
“…The majority of studies ( n = 15) used formalin‐fixed paraffin‐embedded tissue samples for diagnosis and HPV testing. Most studies ( n = 14) used polymerase chain reaction (PCR)‐based test to detect HPV DNA, while two studies used in situ hybridization (ISH) and one study used hybrid capture 2 (HC2). Finally, one study used p16 immunohistochemistry (p16 IHC) as a surrogate marker for HPV infection …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies ( n = 15) used formalin‐fixed paraffin‐embedded tissue samples for diagnosis and HPV testing. Most studies ( n = 14) used polymerase chain reaction (PCR)‐based test to detect HPV DNA, while two studies used in situ hybridization (ISH) and one study used hybrid capture 2 (HC2). Finally, one study used p16 immunohistochemistry (p16 IHC) as a surrogate marker for HPV infection …”
Section: Resultsmentioning
confidence: 99%
“…Finally, the complete absence of clinical and follow‐up data prevents obtaining any conclusions on the prognostic implications of HPV status. Although there are some discordant results on the prognostic significance of HPV in VSCC, recent evidence indicates a strong association between positive p16 IHC and lower FIGO stage and negative lymph node metastasis, and that the presence of HPV DNA or positive p16 IHC is an independent prognostic factor …”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that these two different types of VSCC not only have different epidemiological, clinical, pathological and molecular characteristics, but also a different clinical behavior. These differences stress the need of considering HPV‐associated and ‐independent vulvar tumors as two separate entities …”
Section: Introductionmentioning
confidence: 99%
“…Recurrence rate is higher in pre-malignancies caused by HPV, but less progression to invasive tumours is observed. [24,25]. However, some studies have shown that HPV indicates a less aggressive tumour form with less potential of recurrence [26,27].…”
Section: Discussionmentioning
confidence: 99%